(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the digitalization of social policy in the Kyrgyz Republic, highlighting its opportunities, benefits, and risks. The study covers the impact of digital technologies on public administration, social protection, healthcare, and education. It analyzes digital infrastructure, e-services, the Tunduk mobile application, and their effects on accessibility, convenience, and public awareness. The study also addresses issues of digital inequality, cybersecurity, and data protection.